HIV in Elderly Patient - Fatmala, Galuh Dyah; Claramita, Mora; Rusetiyanti, Nurwestu (Faculty of Medicine, Public Health, and Nursing, 2024)
The patient is 66-year-old men from a small village in the foot of the Merapi volcano, Java Island, Indonesia. He is a husband and a father of three children with three granddaughters. He describes his life as a happy snack fruit farmer, adores living with his caring wife and enjoying role as a mosque priest in his village. But all are disrupted as his health condition has worsened in the past year. Previously, he has been hospitalized twice with the final diagnosis of chronic obstructive pulmonary disease; the tuberculosis has been ruled out by acid fast bacillus test since he also presenting with significant weight loss. Otherwise, he also has multiple visits to dermatologist due to itchy all over his body which is not improving with primary health center (puskesmas) medication. For his blurry eyes, he has been referred by his general practitioner to the ophthalmologist to be suspected with glaucoma and have lanatoprost medication for his eyes daily. He is also having diagnosis of lumbago with sciatica by neurologist since both of his legs are always sore and tingling. All of his outpatient visits and hospitalizations are covered by government health coverage in the same hospital as he has been referred by puskesmas.